PENGARUH UKURAN PERUSAHAAN, OPINI AUDITOR TERHADAP AUDIT DELAY - Wandani, Fanisa Tris; Shiyammurti, Nastiti Rizky; Saputri, Dwi Anggraeni (Journal of Accounting Taxing and Auditing (JATA), 2023)
Abstract This study aims to examine the effect of firm size, profitability and auditor’s opinion on audit delay. The sampling technique used was purposive sampling. The data collected is secondary data. Prior to data analysis, prerequisite analysis tests were carried out which included normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests. The data analysis technique used is multiple linear regression analysis. Based on the X1 t test, it can be seen that the size of the company is 0.014 which is smaller than 0.05. It can be concluded that company size has a significant effect on audit delay, then H1 is accepted. Based on the X2 t test, it is known that the audit opinion is 0.013 which is less than 0.05. It can be concluded that audit opinion has a significant effect on audit delay, then H2 is accepted. Â Keywords: Company Size, Profitability, Auditor Opinion, Audit Delay Â Abstrak PenelitianÂ iniÂ bertujuanÂ untukÂ mengujiÂ pengaruhÂ ukuranÂ perusahaan,Â profitabilitasÂ danÂ opiniÂ auditorÂ terhadapÂ auditÂ delay.Â TeknikÂ pengambilanÂ sampelÂ yangÂ digunakan adalahÂ purposiveÂ sampling.Â DataÂ yangÂ dikumpulkan merupakan data sekunder.Â SebelumÂ dilakukanÂ analisisÂ dataÂ terlebih dahulu diadakanÂ pengujianÂ prasyaratÂ analisis yangÂ meliputiÂ ujiÂ normalitas,Â ujiÂ multikolinieritas,Â ujiÂ heteroskedastisitasÂ danÂ uji autokorelasi.Â Teknik analisisÂ dataÂ yangÂ digunakanÂ adalahÂ analisis regresiÂ linierÂ berganda.Â Â Â Berdasarkan ujiÂ tÂ X1 dapat diketahuiÂ bahwaÂ ukuran perusahaanÂ sebesarÂ 0.014 lebihÂ kecilÂ dariÂ 0.05. Â HalÂ iniÂ dapatÂ disimpulkanÂ bahwa ukuran perusahaanÂ berpengaruh signifikan terhadapÂ auditÂ delay,Â makaÂ H1diterima. Berdasarkan ujiÂ tÂ X2 diketahuiÂ bahwaÂ opini auditÂ sebesarÂ 0.013 Â lebih Â kecil Â dari Â 0.05. Hal Â ini Â dapat Â disimpulkan Â bahwa Â opini auditÂ berpengaruhÂ signifikanÂ terhadap auditÂ delay, makaÂ H2Â diterima. Â KataÂ kunci:Â UkuranÂ Perusahaan,Â Profitabilitas, OpiniÂ Auditor,Â Audit Delay Â